Motivation to learn and social support determine employability among vocational high school students - Fatwa Tentama; Subardjo Subardjo; Muhamad Hasan Abdillah (International Journal of Evaluation and Research in Education (IJERE), 2019)
One of the factors that influence the level of employability is the motivation to learn and social support. This study aims to determine the effect of motivation to learn and social support on student employability. The participants in this study were 255 students of class XII in State Vocational High School 1 Kalasan Yogyakarta, obtained through random cluster sampling. The data collection was carried out by using an employability scale, motivation to learn scale and social support scale. The data analysis used in this study was multiple linear regression analysis. Our data analysis shows that motivation to learn and social support have a very significant effect on employability, seen through the F test that obtained a score of 44.798 and a significance level (p) of 0.000 (p <0.01). In other words, the level of employability could be predicted based on students' level of motivation to learn and social support.